A review on maternal and perinatal outcome of abruptio placenta in Hospital Universiti Sains Malaysia, Kelantan - Sasudin, Nor Liyana Mohamad (2023)
Background: Abruptio placenta is one of the most common etiologies of antepartum hemorrhage. Because of its detrimental feto-maternal effect, this study aimed to identify the risk factors, maternal and neonatal outcomes of abruptio placenta by comparing them with cases without abruptio placenta who delivered within the same years. Methodology: This was a 13-year retrospective case-control study of abruptio placenta in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan in January 2008 until December 2020. Out of 288 cases of abruptio placenta recorded, only 223 cases fulfilled the inclusion and exclusion criteria. Systemic random sampling method was applied to recruit 150 cases of abruptio placenta and another 150 cases of non-abruptio placenta cases. The sociodemographic data, maternal and neonatal outcomes were recorded and analysed using SPSS version 27. Results: The incidence of abruptio placenta in our study is 288 cases out 103,042 of deliveries (0.3%). As for the risk factors, patients with pre-eclampsia (adj OR 4.656, 95% CI 2.214-9.789, p<0.001), PPROM (adj OR 5.377, 95% CI 1.854-15.596, p=0.002) and history of abdominal massage (adj OR 10.491. 95% CI 1.188-92.636, p=0.034) had significant increased risk for abruptio placenta. In term of pregnancy outcome, the caesarean section rate was higher in the abruptio placenta group as compared to non-abruptio placenta cases (p<0.001). These correlate with the severity of abruptio placenta cases in which 70 (46.7%) were in grade 2 abruptio placenta and 11 (7.3%) were in grade 3 group. In this study, the incidence of PPH was higher in the abruptio placenta group 81 (54.0%) whereas only 31 cases (20.7%) in the control group (p<0.001). 10 (6.7%) patients in the abruptio placenta group had DIVC as compared to only one (0.7%) case in the non-abruptio group (p=0.006). There were 54 cases (36.0%) that required blood transfusion in the abruptio placenta group and 15 cases (10.0%) in the non-abruptio placenta cases (p<0.001). 16 (10.7%) of abruptio placenta cases required ICU admission whereas there were only four (2.7%) cases in the control group (p=0.005). As for the perinatal outcome, high rate of preterm deliveries was observed in the abruptio placenta group (p<0.001). Newborn in the abruptio placenta group had higher rate of NICU admission (p<0.001), Apgar score less than 7 in 5 minute (p<0.001) and stillbirth (p<0.001) as compared to the control group. There were four cases of early neonatal death in the abruptio placenta group in this study p=0.176. Conclusion: This study showed that pre-eclampsia, PPROM and history of abdominal massage are significant risk factors of abruptio placenta. There was statistically significant difference in the maternal complications (PPH, DIVC, blood transfusion and ICU admission) and perinatal outcome (prematurity, Apgar score less than 7 in 5 minute, NICU admission and stillbirth).